Financialization in the Light of Keynesian Theory - Amit Bhaduri (PSL Quarterly Review, 2011)
Episodes of financial crises are usually recognizable as belonging to a general pattern despite their different historical specificities. The present essay attempts to isolate and understand the recurring common features of several recent crises in advanced market economies in the light of Keynesian theory with some crucial modifications introduced later, particularly by Kaldor and Minsky with respect to the financial sector. While financial innovations are devised continuously to escape regulations on the formal credit system by creating substitutes for bank credit, fragility increases along with the internal illiquidity of the financial system. The proclivity of the system to financial crisis arising from negative shocks can be understood against the background of systemic illiquidity coupled with rapid expansion of a range of credit substitutes in a network of tightly interlocked assets of financial firms.